Agility in team sports: Testing, training and factors affecting performance - Paul, D. J.; Gabbett, T. J.; Nassis, G. P. (Sports Medicine, 2016)
Background: Agility is an important characteristic of team sports athletes. There is a growing interest in the factors that influence agility performance as well as appropriate testing protocols and training strategies to assess and improve this quality.